The Long non-coding RNA MALAT1 functions as a competing endogenous RNA to regulate vascular remodeling by sponging miR-145-5p/HK2 in hypertension - Jiangyong Yang; Guojun Jiang; Ling Huang; Zhongyi Liu; Rengui Jiang; Gang Cao; Jun Cao; Hengqing Zhu; Lemei Chen; Xiaoming Chen; Fang Pei (Clinical and Experimental Hypertension, 2023)
ABSTRACTLong non-coding RNAs (LncRNAs) have been found to play a regulatory role in the pathophysiology of vascular remodeling-associated illnesses through the lncRNA-microRNA (miRNA) regulation axis. LncRNA metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) is thought to be involved in proliferation, migration, apoptosis, and calcification of vascular smooth muscle cells (VSMCs). The purpose of this study was to investigate the regulatory role of MALAT1 on vascular remodeling in hypertension. Our data indicate that the expression of MALAT1 is significantly upregulated in hypertensive aortic smooth muscle. Knockdown of MALAT1 inhibited the proliferation, migration, and phenotypic transition of VSMCs induced by Ang II. Bioinformatics analysis was used to predict the complementary binding of miR-145-5p to the 3’-untranslated region of MALAT1. Besides, the expressions of MALAT1 and miR-145-5p were negatively correlated, while luciferase reporter assays and RNA immunoprecipitation assay validated the interaction between miR-145-5p and MALAT1. The proliferation, migration and phenotypic transformation of VSMCs induced by overexpression of MALAT1 were reversed in the presence of miR-145-5p. Furthermore, we verified that miR-145-5p could directly target and bind to hexokinase 2 (HK2) mRNA, and that HK2 expression was negatively correlated with miR-145-5p in VSMCs. Knockdown of HK2 significantly inhibited the effects of overexpression of MALAT1 on Ang II-induced VSMCs proliferation, migration and phenotypic transformation. Taken together, the MALAT1/miR-145-5p/HK2 axis may play a critical regulatory role in the vascular remodeling of VSMCs in hypertension.